OBSTACLES AND ENABLERS FOR THE DEVELOPMENT OF A NATIONAL ACTION PLAN FOR THE UNITED NATIONS SECURITY COUNCIL RESOLUTION 1325 (2000) IN SOUTH AFRICA - Dhlamini, Lindiwe (My University, 2014)
The purpose of this research was to determine how South Africa can further implement the United Nations Security Council’s landmark Resolution 1325 on women, peace and security that was adopted by the Security Council at its 4213th meeting on 31 October 2000. The report will achieve this by ascertaining the obstacles and enablers for the development of a National Action Plan (NAP) in order to implement the aforementioned resolution in the country. It has been 11 years since the adoption of the resolution. During this period fewer than 30 countries out of 192 Member States have developed NAPs (Peace Women 2011). This realisation is considered to be inadequate, and contributes to the persistent victimisation of women by means of gender-based violence and discrimination with regards to armed conflict and its repercussions. The research data was collected through both face-to-face and in-depth telephonic interviews that were arranged with relevant employees at the UN, SA government departments, individuals based at embassies that have already implemented the UNSCR 1325 and within civil society, all based in SA. It was found that the absence of a NAP in SA, unemployment and HIV prevalence hinders the advancement of women empowerment and gender equality; that obstacles to the development of a NAP include a lack of monitoring and accountability; and that NAP enablers include partnerships between UN agencies, governments and civil society, access to private sector CSR programmes, and recognition of female activists, for example in the awarding of Nobel prizes. The years 2010-2020 have been posited as the Decade of the African Women (African Union 2009). The basis for this report, should therefore, be viewed as the opportune time to attempt to further advance concerns regarding women, peace and security within SA, Southern African Development Community and the African Union. This can arguably be done through developing NAPs, and it should be noted that the process of developing a NAP is as important as the final product
MBA thesis
Keywords: Women, United Nations Declaration on; United Nations Declarations